Effect of lanthanum ions on the various limiting, linear, and nonlinear optical properties of triple blended polymers (PVA/PVP and PEG) - Mohammed, M. I.; Zahran, H. Y.; Alabdulaal, T. H.; Zyoud, Samer H.; Shahwan, Moad; Aydin, Cihat; Yahia, I. S. (Elsevier, 2024)
PVA 70%, PVP 20%, and 10% PEG Polymer blend containing varying amounts of La(NO3)3 (x wt% = 0.3, 1.5, 2, 3, 4.5, 6) were created. X-ray diffraction (XRD) data was analyzed to identify the structural and microstructural parameters characteristic of La(NO3)3 salt filler. FTIR was used to analyze the salt filler's complexation over the blended polymer matrix. The UV-visible-NIR spectrophotometer discussed how different La+3- ion loadings affected the blend polymer's optical properties (absorbance, absorption edge, extinction coefficient, dielectric, and optical conductivity). Absorption edge, Tauc relation, absorption spectra fitting, and the dielectric permittivity's imaginary part were utilized to compute the optical gap Eg of the films precisely. By incorporating La3+ions at concentrations ranging from 0.0 to 6.0 wt%, the optical gap Eg of the (PVA-PVP-PEG)/La3+ composites was decreased. It has also been reported that La(NO3)3 salt has an impact on high-frequency (epsilon infinity) and staticfrequency (epsilon o) dielectrics in addition to the extinction coefficient and refractive index. Increasing the amount of La(NO3)3 salt in the blend improved its nonlinear refractive index and optical susceptibilities (chi(1), and chi(3)). Both 632.8 nm He-Ne laser beam and 532 nm solid-state green diode laser beam are used to test the optical limitations of the samples. The clear improvements were seen in the optical absorption measurements after La (NO3)3 salt was added. Since the (PVA-PVP-PEG)/La(NO3)3 film has a higher refractive index, it is possible to use this polymer blend as a cladding for optoelectronic applications.
Keywords: PVA-PVP-PEG) blend matrix; Lanthanum (III) nitrate; XRD; FTIR; UV-Vis -IR spectrometer; Linear and nonlinear optical parameters; And optical limiting